2023
DOI: 10.1097/ta.0000000000004163
|View full text |Cite
|
Sign up to set email alerts
|

When Is It Safe to Start VTE Prophylaxis after Blunt Solid Organ Injury? A Prospective AAST Multi-Institutional Trial

Morgan Schellenberg,
Natthida Owattanapanich,
Brent Emigh
et al.

Abstract: Background The optimal time to initiate venous thromboembolism (VTE) chemoprophylaxis (VTEp) after blunt solid organ injury remains controversial as VTE mitigation must be balanced against bleeding promulgation. Evidence from primarily small, retrospective, single-center work suggests VTEp ≤48 h is safe and effective. This study was undertaken to validate this clinical practice. Methods Blunt trauma patients presenting to 19 participating trauma centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Adult trauma literature has shown that early initiation of cVTE after trauma reduces the incidence of VTE, even in the presence of solid organ injuries and traumatic brain injury . This study also suggests that the greatest reduction in VTE risk may be seen when cVTE is used early following traumatic injury.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Adult trauma literature has shown that early initiation of cVTE after trauma reduces the incidence of VTE, even in the presence of solid organ injuries and traumatic brain injury . This study also suggests that the greatest reduction in VTE risk may be seen when cVTE is used early following traumatic injury.…”
Section: Discussionmentioning
confidence: 55%
“…Adult trauma literature has shown that early initiation of cVTE after trauma reduces the incidence of VTE, even in the presence of solid organ injuries and traumatic brain injury. [31][32][33][34] This study also suggests that the greatest reduction in VTE risk may be seen when cVTE is used early following traumatic injury. We found that median (IQR) time from admission to initiation of cVTE was significantly different between patients who developed VTE (4.2 days [2.5-7.5 days]) and those without VTE (2.5 days [1.0-4.0 days]; P = .008).…”
Section: Discussionmentioning
confidence: 99%
“…Despite increasingly detailed efforts to optimize prophylaxis, venous thromboembolism (VTE) remains a leading cause of morbidity and mortality after traumatic injury. Over the last two decades, landmark studies have improved the efficacy of prophylaxis by identifying the utility of anti-Xa guidance for enoxaparin dose adjustment 1 and individualized enoxaparin dosing 2 ; sped the initiation of safe prophylaxis in patients with traumatic brain injury 3 or blunt solid organ injury 4 ; demonstrated the increased VTE risk that occurs when medication doses are missed 5 ; and enlisted patients and nurses in multidisciplinary educational efforts to improve medication adherence. 6 Despite these efforts, morbidity and mortality from VTE remain unacceptably high, and additional improvements are needed.…”
mentioning
confidence: 99%